Strategic Alignment in Times of Crisis: Voting at the Dawn of a Global Pandemic - Arndt Leininger; Max Schaub (Political Behavior, 2024)
Natural disasters are likely to increase in the near future. How does the emergence of such events influence voting behavior? While the literature has focused on the electoral repercussions after disaster has already struck, we investigate whether imminent disaster influences vote choice. We study the effect of the onset of the COVID-19 pandemic on electoral choice in a setting that allows for causal identification: the local elections in Germany's southern state Bavaria in March 2020, where, at the time of the elections, only an as-if random sample of localities had recorded cases of COVID-19. We find that initial local outbreaks favored the political party governing at the state level and hurt the far right. These findings are most likely driven by a `strategic alignment' mechanism, whereby voters choose the party or candidate they believe is best placed to help them through the crisis.
Keywords: 320